h - Preneel, Bart.; Takagi, Tsuyoshi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the proceedings of the 13th International Workshop on Cryptographic Hardware and Embedded Systems, CHES 2011, held in Nara, Japan, from September 28 until October 1, 2011. The 32 papers presented together with 1 invited talk were carefully reviewed and selected from 119 submissions. The papers are organized in topical sections named: FPGA implementation; AES; elliptic curve cryptosystems; lattices; side channel attacks; fault attacks; lightweight symmetric algorithms, PUFs; public-key cryptosystems; and hash functions.
Keywords: Computer science; Data protection; Data structures (Computer science).; Data encryption (Computer science).; Coding theory; Computer software; Computational complexity; Computer Science; Data Encryption; Coding and Information Theory; Data Structures, Cryptology and Information Theory; Systems and Data Security; Algorithm Analysis and Problem Complexity; Discrete Mathematics in Computer Science